A Micro-History of Victorian Liberal Parenting John Morley's "Discreet Indifference" - Morrison, Kevin A. (Springer International Publishing, 2018)
This book explores the theory and practice of Victorian liberal parenting by focusing on the life and writings of John Morley, one of Britain's premier intellectuals and politicians. Reading Morley's published works-much of which explicitly or implicitly addresses this relationship-with and against other writings of the period, and in the context of formative circumstances in his own life, it explores how living one's life as a liberal extended to parenting. Although Victorian liberalism is currently undergoing reappraisal by scholars in the disciplines of literature and history, only a handful of studies have addressed its implications for intimate personal relations. None have considered the relationship of parent and child. Four of the chapters document how John Morley was parented and how he defined himself as a parent, based on newly available archival materials. Two other chapters analyze his many writings on or concerned with parenting and parenthood. .